Measuring Wine Quality and Typicity. - Marianthi Basalekou*; Panagiotis Tataridis; Konstantinos Georgakis; Christos Tsintonis (Beverages, 2023)
Wine quality and typicity are complex concepts that can be hard to define. Wine is a product destined to not only be consumed and appreciated but also marketed, and its distinctiveness, quality and typicity are important characteristics that describe a wine’s sensory profile and, ultimately, add value to the finished product. Even though both quality and typicity are mostly assessed using a sensory evaluation, many studies have examined the feasibility of using chemical analysis methods in order to increase the objectivity of assessments. Today, the use of chemometrics facilitates the handling of big data, and outcomes from various analytical techniques can be integrated to produce more accurate results. This study discusses the existing sensory and analytical approaches, implications and future prospects for an objective measurement of quality and typicity as well as methods for the selection of appropriate data for predictive model development.